2019
DOI: 10.29313/gmhc.v7i2.4087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Noni (<i>Morinda citrifolia</i> L.) Leaf Extract Paste in Carrageenan-induced Paw Edema on Wistar Rats

Abstract: The inflammatory response is one of natural process in the body to protect itself following tissue injury, but it can cause discomfort. Noni (Morinda citrifolia L.) leaf known as a traditional medicament to help reduce the inflammatory effect. The leaves empirically applied as a wrapping on fever or wound. The purpose of this study was to identify the anti-inflammatory effect of topical noni leaf extract paste in 5% and 10% concentration by examination of Wistar rat paw edema induced by λ-carrageenan. Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Even though there were changes in the number of fibroblasts but no significancies showed by two-way ANOVA (sig 0.885, a 5%). This result is in line with a report that showed no significant effect of noni's extract against the number of fibroblast cells 6 . In their report, the number of fibroblasts in the control group was higher than in all treatment groups, although it was not statistically significant.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Even though there were changes in the number of fibroblasts but no significancies showed by two-way ANOVA (sig 0.885, a 5%). This result is in line with a report that showed no significant effect of noni's extract against the number of fibroblast cells 6 . In their report, the number of fibroblasts in the control group was higher than in all treatment groups, although it was not statistically significant.…”
Section: Resultssupporting
confidence: 93%
“…This indicates that the proliferation of fibroblast cells in all treatment groups has decreased earlier than in the control group. This phenomena could be explained that occurrence of fibrosis was subjected to the inflammatory response classified as acute and chronic inflammation, which differs from their vascular reactions, cells involved, and duration 6 . Another report also showed that a remodelling phase of wound healing, fibroblast cell proliferation decreases as collagen fibres are synthesized 12 Figure 3 indicates that the variety of NLEE had no significant effect on the wound diameter and healing time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation